Functional genomic analysis of K+ related salt-responsive transporters in tolerant and sensitive genotypes of rice - Haque, Umme Sabrina; Elias, Sabrina M.; Jahan, Israt; Seraj, Zeba I. (Frontiers in Plant Science, 2023)
Salinity is a complex environmental stress that affects the growth and production of rice worldwide. But there are some rice landraces in coastal regions that can survive in presence of highly saline conditions. An understanding of the molecular attributes contributing to the salinity tolerance of these genotypes is important for developing salt-tolerant high-yielding modern genotypes to ensure food security. Therefore, we investigated the role and functional differences of two K+ transporting salt-responsive transporters selected from previously identified QTLs from the tolerant rice landrace genotype (Horkuch) and sensitive genotype (IR29). In silico comparative sequence analysis of these genes between Horkuch and IR29 showed some significant differences in promoter sequences which may give a survival advantage to Horkuch under salt-stress. Real-Time expression analysis of the selected genes was performed in leaves and roots of IR29 (salt-sensitive), I-14 and I-71 (Recombinant Inbred Lines of IR29(♀)× Horkuch), Horkuch and Pokkali (salt-tolerant) under salt-stress at different time points. OsTPKa (Vacuolar two-pore potassium channel) and OsHAK_like (a hypothetical protein of HAK family) were found to be overexpressed in tolerant varieties (Horkuch and Pokkali). Moreover, a coordinated expression pattern between these two genes was observed in tolerant Horkuch under salt-stress. For further insight, the overexpressers, OsTPKa and OsHAK_like were chosen for loss-of-function genomic analysis in Horkuch using the CRISPR/Cas9 tool. Independently transformed plants where the expression of these genes was significantly lowered, performed poorly in physiological tests for salinity tolerance, supporting the assumption that loss of function of OsTPKa and OsHAK_like will likely cause an increase in the salt sensitivity of Horkuch. Furthermore, OsTPKa was chosen for cloning into a sensitive variety by Gateway technology to observe the effect of gain-of-function. Positively transformed T0 plants consistently showed growth advantage under both control and salt stress. The information gained from this study confirms the role of these two transporters in defending against salt stress, minimizing salt injury, and maintaining plant growth.